Determination of heavy metals in water, sediment and fishes of Bakun Hydroelectric Reservoir - Wong, Yiew Ee (Universiti Malaysia Sarawak, (UNIMAS), 2015)
In this study, the concentration of selected metals (Cd, Cu, Fe, Hg, Mn, Se and Zn) in water, sediment and fishes of Bakun hydroelectric reservoir and the adjacent vicinity were determined. Heavy metals were analysed using a flame atomic absorption spectrophotometer and a mercury analyser. In water, only Fe, Mn and Hg were detected in the order of Fe > Mn > Hg. In sediment, Fe, Mn, Zn, Cu, and Hg were detected in the order of Fe > Mn > Zn > Cu > Hg. In fish, metals were detected in the order of Mn > Zn > Fe > Cu. The sediment was considered unpolluted according to the contamination factor, geo-accumulation index and pollution load index nonetheless the concentrations of Fe and Mn would require conventional treatment for drinking water purpose. Heavy metals in fish were generally below the permissible level of WHO/FAO except Mn where the average was found above 5.5 mg/kg.